Organic Waste Management OBIN / Eiman Haziq Ahmad Nizam - Ahmad Nizam, Eiman Haziq (2020)
In Organic Waste Management, our aim is always trying to reduce the waste in Malaysia in a creative way. OBIN is a product where our customer can make their own fertilizers just by using their food waste at their house. It contains catalyst that helps food waste turn into organic fertilizers. For better storage of the fertilizer products it comes with a cooling system to reduce the smell of the fertilizers. OBIN is targeted to all middle to higher income level in Malaysia who’s attracted to home gardening. In comparison to other product which already in the market. With the uniqueness that OBIN have we believed it can strive through the market and made changes to the world.